Numerical modeling for the upper crustal deformation in the Southern Andes - Quinteros, J. (2005)
In this work, the modeling of plate tectonic processes associated with crustal deformation through a numerical framework for non-collisional Andean type orogens is presented. The main objectives of the numerical framework are to develop a numerical model in order to represent large-scale deformation in Andean type subduction zones, to include appropriate physical and mathematical laws that describe the behavior of the lithosphere, to model surface erosion taking into account dominant winds direction and the synorogenic topography of the orogen as the crustal erosion caused by friction between the subducting and the overriding plate and to include isostatic compensation behavior taking into account flexural rigidity. © 2005 Asociación Geológica Argentina.